1999
DOI: 10.1016/s0895-7061(99)00053-9
|View full text |Cite
|
Sign up to set email alerts
|

Matrix study of irbesartan with hydrochlorothiazide in mild-to-moderate hypertension

Abstract: The purpose of this study was to assess the safety and antihypertensive dose-response effects of irbesartan and hydrochlorothiazide (HCTZ) in patients with mild-to-moderate hypertension. After a 4- to 5-week single-blind placebo lead-in period, 683 patients with seated diastolic blood pressure (SeDBP) between 95 and 110 mm Hg were randomized to receive once-daily dosing with one of 16 different double-blind, fixed combinations of irbesartan (0, 37.5, 100, and 300 mg irbesartan) and HCTZ (0, 6.25, 12.5, and 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 19 publications
8
99
0
2
Order By: Relevance
“…A similar corrective effect on serum potassium levels has also been observed when irbesartan, another AT 1 receptor antagonist, is co-administered with HCTZ. 17 In conclusion, our study has shown that oncedaily treatment with a fixed-dose combination of telmisartan 80 mg/HCTZ 12.5 mg offers superior efficacy to telmisartan 80 mg in patients with mild-tomoderate hypertension uncontrolled on telmisartan alone. This fixed-dose combination is also well tolerated.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…A similar corrective effect on serum potassium levels has also been observed when irbesartan, another AT 1 receptor antagonist, is co-administered with HCTZ. 17 In conclusion, our study has shown that oncedaily treatment with a fixed-dose combination of telmisartan 80 mg/HCTZ 12.5 mg offers superior efficacy to telmisartan 80 mg in patients with mild-tomoderate hypertension uncontrolled on telmisartan alone. This fixed-dose combination is also well tolerated.…”
Section: Discussionmentioning
confidence: 61%
“…For example, activation of the renin-angiotensin-aldosterone system (RAAS) by HCTZ amplifies the effects of agents acting through blockade of this pathway, including AT 1 receptor antagonists. [16][17][18][19][20][21] Combination of HCTZ with agents acting on the RAAS also has the potential to ameliorate the potassium depletion commonly associated with thiazide diuretic therapy. 17,22,23 A fixed-dose combination of telmisartan 80 mg/HCTZ 12.5 mg has been developed for the treatment of patients with mild-to-moderate hypertension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][36][37][38][39][40][41][42] The only biochemical variable that is affected by most antihypertensive diuretics irrespective of the dose is serum uric acid concentration, which undergoes a small increase, on average, even when low doses are used. 13,21,43 Cicletanine 50 mg does not modify the renal handling of urate, 44 and it does not elevate serum uric acid concentration.…”
Section: Safety Of Diuretics At Low Dosesmentioning
confidence: 99%
“…The angiotensin II receptor antagonist losartan has been found to increase the renal excretion of urate in healthy subjects, 95 and both losartan and irbesartan have been found to attenuate hydrochlorothiazide-induced increases in serum uric acid in hypertensive patients. 96,97 Changes in acid-base balance Potassium-retaining diuretics cause renal retention of hydrogen ions and thereby tend to provoke acidosis, 48 particularly in patients at risk such as individuals who present renal insufficiency, subjects who also suffer from insulin-dependent diabetes and elderly persons.…”
Section: Hyperuricaemiamentioning
confidence: 99%